PEMIKIRAN FEMINIS MUSLIM DI INDONESIA TENTANG FIQH PEREMPUAN - M. Noor Harisuddin (AL-TAHRIR, 2015)
Abstract: In the last three decades, there has been a transformation of society from a patriarchal society towards gender equality in Indonesia. Dissent on sex and gender  has been increasing in the hands of Indonesian Muslim feminist thinkers. Sex and gender distinction  between man and women as a nature of God on the one hand and gender as a cultural construct on the other hand gave rise to at least three mainstreams of thought of  feminist Muslims in Indonesia; sex and gender are coextensive, women are human females, men are human males.  Through gender-based realm of women fiqh (jurisprudence), this study tried to explore the Indonesian Muslim mainstream feminist thought related to gender equity. Through a number of data scattered in a number of works that appeared in three Muslim feminists of Indonesia, namely, Ratna Megawangi, Husayn Muhammad, and Muchith Muzadi, it could be illustrated that, firstly, sex and gender were two things in common or in other word the distinction between sex and gender turns out to be no distinction at all. It meant that the distinction of men to women was natural which was in Islam called ‘sunnat Allah’ and the ‘equality’ should be interpreted as ‘sunnat Allah’ too; secondly, both sex and gender are two different things, the former was the nature of God, while the latter was the result of cultural constructs so that each should be seated in its own respective positions through new perspectives far beyond the perspective of classical  scholars; thirdly, although there was distinction between sex and gender,  they should be positioned in their respective places without denying the perspective of classical scholars الملخص :في العقود الثلاثة الماضية، كان هناك تحول المجتمع على نطاق واسع في إندونيسيا.  أي الناس الذي يرأسهم سابقا المجتمع الأبوي بين الجنسين. ومن المثير للاهتمام ، شارك الإسلام - وهو دين الأغلبية في إندونيسيا - في عملية هذا التحول . وهناك عدد كثير من المفكرين النسوي الإسلامي في إندونيسيا مع مجموعة من الأفكار المختلفة ، ولكن لا يزال مع الالتزام نفسه ، وهي لرفع كرامة المرأة في إندونيسيا . و شاركت نظرية فقه النساء  من جزء " الدراسات الإسلامية " في فكرة أن هناك  المساواة بين الجنسين في إندونيسيا . Abstrak: Dalam tiga dasawarsa terakhir, terjadi transformasi masyarakat di Indonesia dari patriarki menuju masyarakat yang berkesetaraan gender. Pergumulan antara sex dan gender ini makin meningkat di tangan pemikir feminis muslim Indonesia. Diferensiasi antara sex laki-laki dan perempuan sebagai sebuah kodrat Tuhan di satu sisi dengan gender sebagai sebuah konstruk budaya di sisi yang lain memunculkan paling tidak tiga mainstream pemikiran feminis muslim di Indonesia. Melalui ranah gender yang berbasis fiqh perempuan, kajian ini mencoba untuk mengeksplorasi mainstream pemikiran feminis muslim Indonesia terkait kesetaraan gender. Melalui sejumlah data yang berserakan dalam sejumlah karya yang dimunculkan tiga feminis muslim Indonesia yakni Ratna Megawangi, Husain Muhammad, dan Muchith Muzadi dapat diilustrasikan bahwa, pertama sex dan gender adalah satu hal yang identik dan ini berarti bahwa diferensiasi laki-laki dengan perempuan merupakan hal yang natural, sunnat Alla>h dan kesetaraan harus dimaknai sebagai sunnat Alla>h; kedua sex dan gender merupakan hal yang berbeda, yang pertama merupakan kodrat Tuhan, sedangkan yang kedua adalah hasil konstruk budaya, karenanya harus didudukkan pada posisi masing-masing melalui cara pandang baru, melalmpaui cara pandang ulama klasik; ketiga walaupun terdapat deferensiasi antara sex dan gender, namun keduanya harus diposisikan pada tempatnya masing-masing tanpa harus menafikan perspektif ulama klasik.   Keywords: perempuan, feminis, konservatif, liberal, moderat, fiqh perempuan.